OPTIMALISASI PERAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM BIDANG PENGAWASAN PEMERINTAH DESA - Fisip PAsira; Ade Irma Suryani (Jurnal PAsira, 2020)
ABSTRACT This study aims to determine the Optimization of the Role of Village Consultative Bodies is the Field of Supervision of the Village Government especially the supervision of the Village Consultative Body in the implementation of village development. This research uses descriptive qualitative method, data collection techniques throught by in-depth interview, observations, and documentation studies.The data analysis technique uses stages of Data Collection, Data Reduction, Data Presentation and Verification. Based on the results of research conducted by researchers, it can be concludeed that the Optimization of the Role of Village Consultative Bodies in the Field of Village Government Oversight (Case Study in Ketuan Jaya Village, Muara Beliti District, Musi Rawas District) is not optimal. Thi is because in the supervision indicators on the results of planning, overseeing the formulation of main function and overseeing the organization structure, supervision by the Village Consultative Body is not carried out and not even the administration of the results of the indicators is not administrered. Keywords: Optimization; Role of BPD; Supervision; Village Government ABSTRAK Penelitian ini bertujuan untuk mengetahui Optimalisasi Peranan Badan Permusyawaratan Desa di Bidang Pengawasan Pemerintah Desa khususnya pengawasan Badan Permusyawaratan Desa dalam pelaksanaan pembangunan desa. Penelitian ini mengunakan metode deskriptif kualitatif, teknik pengumpulan data dengan cara wawancara mendalam, observasi dan studi dokumentasi. Teknik analisis data menggunakan tahapan Pengumpulan Data, Reduksi Data, Penyajian Data, dan Verifikasi. Berdasarkan hasil penelitian yang dilakukan peneliti maka dapat disimpulkan bahwa Optimalisasi Peranan Badan Permusyawaratan Desa Di Bidang Pengawasan Pemerintah Desa (Studi Kasus Di Desa Ketuan Jaya Kecamatan Muara Beliti Kabupaten Musi Rawas) tidak optimal. Hal ini dikarenakan dalam indikator pengawasan terhadap hasil perencanaan , mengawasi dalam perumusan tupoksi dan mengawasi dalam pembuatan struktur organisasi tidak dilakukan Pengawasan oleh Badan Permusyawaratan Desa bahkan tidak teradministrasinya hasil dari pencapaian perindikator tersebut. Kata Kunci: Optimalisasi; Peranan BPD; Pengawasan; Pemerintah Desa